2017
DOI: 10.4067/s0719-81322017000300185
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Spirulina platensis ( Arthrospira platensis ) and Saccharomyces cerevisiae on the distribution and cytokine production of CD4+ and CD8+ T-lymphocytes in rabbits

Abstract: ABSTRACT. Natural additives have become one of the most alternative immune enhancer nowadays. In particular, Spirulina platensis (Arthrospira platensis) (SP) and Saccharomyces cerevisiae (SC) have been used for improving the immune system and quality of life. The aim of this study was to regulate the immune effect of S. cerevisiae and S. platensis (A. platensis) combination. Forty male New Zealand white rabbits, aged 5-6 weeks, were analysed in 4 groups: Control (basal diet); SC (added 3 g/kg diet), SP (added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…S. platensis has important contents such as high protein, polyphenols, phycocyanin, minerals and vitamin C (Khan et al, 2005;Seyidoglu et al, 2017). It can be digested easily due to its non cellulose structure on its cell wall, and thereby it enhances growth (Moreira et al, 2011;Seyidoglu and Galip, 2014;Seyidoglu et al, 2017a). Several studies reported the effects of Spirulina on haematological parameters and growth performances in rats (Araujo et al, 2003;Simsek et al, 2007;Promya and Chitmanat, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…S. platensis has important contents such as high protein, polyphenols, phycocyanin, minerals and vitamin C (Khan et al, 2005;Seyidoglu et al, 2017). It can be digested easily due to its non cellulose structure on its cell wall, and thereby it enhances growth (Moreira et al, 2011;Seyidoglu and Galip, 2014;Seyidoglu et al, 2017a). Several studies reported the effects of Spirulina on haematological parameters and growth performances in rats (Araujo et al, 2003;Simsek et al, 2007;Promya and Chitmanat, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, Fouda and Ismail (2017) also reported that adult New Zealand White (NZW) rabbit bucks fed 700 mg SP / diet were significantly (P < 0.01) increased the growth performance parameters than those in the control group. Where, SP can be digested simply due to its non cellulose structure on its cell wall, and thus it enhances of animal growth performance (Moreira et al, 2011;Seyidoglu and Galip, 2014;Seyidoglu et al, 2017b). Contradictory results are possibly due to the different tested levels of SP and quality in the present study.…”
Section: Resultsmentioning
confidence: 70%
“…( Løbner, Walsted, Larsen, Bendtzen, & Nielsen, ) Also, in vivo studies have reported Spirulina extracts can significantly increase lymphocytes counts at the animals' blood samples. (Emami & Olfati, ; Seyidoglu, Galip, Budak, & Uzabaci, ; Simsek, Karadeniz, Kalkan, Keles, & Unal, ) In addition, the enhancement of proliferation and differentiation of bone marrow hematopoietic cells by Spirulina extract is another reason of lymphocytes number increase in the bone marrow and peripheral blood. (Hayashi et al, ) Moreover, Hayashi et al .…”
Section: Discussionmentioning
confidence: 99%